A49 BUTYRATE PRESERVES THE EPITHELIAL MITOCHONDRIAL NETWORK DISRUPTED BY THE CROHN'S DISEASE PATHOBIONT ADHERENT-INVASIVE E. COLI. (4th March 2021) - Hamed, S; wang, A; Shearer, J; Shutt, T; Mckay, D M
Abstract: Background: Mitochondria exist in a dynamic network that undergoes continuous cycles of fission and fusion that is tightly controlled. Mitochondrial dysfunction is implicated in several autoimmune and inflammatory diseases. Adherent-invasive E. coli (AIEC) is a pathogenic strain of bacteria associated with Crohn's disease (CD), that can evoke pro-inflammatory responses. Data from our lab showed that AIEC (strain LF82) infection in gut epithelial cells (T84 human cell line) caused dramatic mitochondrial network fragmentation and loss of mitochondrial membrane potential. Short chain fatty acids (SCFA) produced by commensal bacteria in the gut have a wide range of benefits including enhancing mitochondrial biogenesis. Aims: To determine (1) if sodium butyrate (NaB) treatment can protect against mitochondrial dysfunction induced by AIEC (strain LF82) infection in T84 epithelial cells and then (2) to identify the mechanism by which NaB restores mitochondrial functions. Methods: We assessed changes in mitochondrial network morphology through confocal microscopy live cell imaging of mitotracker-stained T84 epithelial cells based on unbiased Hoechst-stained nuclei to select the field of view. The effect of NaB on the proliferation of bacteria and their invasion of T84-epithelia was assessed by growth curve analysis and bacterial internalisation assays. Finally, mRNA and protein expression of peroxisome proliferating activator receptor gamma co-activator 1 alpha (PGC1α), a regulator of mitochondrial biogenesis, were assessed by qPCR and Western Blot. Results: We confirmed that AIEC infection (strain LF82, 10 8 cfu, 4h) induces massive mitochondrial fragmentation in T84 cells (2x10 5 ). We also found that cotreatment of T84 cells with NaB (10mM) and LF82 showed increased percentage of fused mitochondrial networks compared to LF82-treated cells. This result was also seen in cells treated with mitochondrial uncoupler dinitrophenol (DNP; 0.1 mM, 2h) and NaB. Moreover, the protective effect of NaB was not related to inhibition of proliferation of the bacteria as we demonstrated that LF82 growth and its invasive phenotype was not compromised by NaB (3-20mM; 0-24hr). In agreement with the effect of LF82 on mitochondrial functions, LF82 significantly reduced PGC1α mRNA expression in T84 cells, that was prevented by co-treatment with NaB. Conclusions: These data suggest the pathogen disruption of the epithelial mitochondrial network is a component of IBD; thus, identifying mitochondrial fission and fusion pathways as novel therapeutic targets to control enteric inflammation. The data underscore the complex interplay between bacteria and the epithelium, such that commensal organisms may preserve the mitochondrial network in the face of challenge from pathogens that seek to disrupt mitochondrial form and function Funding Agencies: CIHR